Combined Signature of the Urinary Microbiome and Metabolome in Patients With Interstitial Cystitis - Xu, Hewei; Tamrat, Nebiyu Elias; Gao, Jie; Xu, Jie; Zhou, Yiduo; Zhang, Sicong; Chen, Zhengsen; Shao, Yunpeng; Ding, Liucheng; Shen, Baixin; Wei, Zhongqing (Frontiers in Cellular and Infection Microbiology, 2021)
Interstitial cystitis (IC) is a clinical syndrome characterized by urinary frequency, urgency and bladder pain or pelvic pain; however, the underlying pathophysiological mechanisms and diagnostic markers are unknown. In this study, microbiome and metabolome analysis were used to explain the urine signatures of IC patients. Urine samples from 20 IC patients and 22 control groups were analyzed by using 16S rRNA sequence and Liquid chromatography coupled with mass spectrometry. Four opportunistic pathogen genera, including Serratia, Brevibacterium, Porphyromonas and Citrobacter, were significantly up-regulated in IC group. The altered metabolites signatures of the metabolome may be related to sphingosine metabolism, amino acid metabolism and fatty acid biosynthesis. Meanwhile, the associations were observed between different metabolites and microbiomes of IC. The present study suggests that the combined signatures of IC in urine microbiome and metabolome may become its prospective diagnostic markers.